TEACHERS AND STUDENTS’ PERCEPTIONS ON THE USE OF ICT IN LEARNING ENGLISH AT A JUNIOR HIGH SCHOOL IN TUBAN - Risa Triassanti; Christina Innocenti Tumiar Panggabean; Budi Susatyo; Agus Wardhono; Yoliete Rohmadtis; Sholahudin Al Magribi (DIDAKTIKA, 2022)
This study focuses on the perceptions of students and teachers regarding the use of ICT media in learning English. This study also aims to determine the attitudes of students and teachers about the use and benefits of ICT media in learning and teaching in English classes and to find out the problemsfaced by teachers when using or operating ICT media in English classes. This study uses a descriptive quantitative approach applying survey. Data was collected from a survey in the form of giving a questionnaire or questionnaire, which involved 10 randomly selected students from grades VI and VII and two English teachers at SMP PGRI 3 Tuban. The quantitative data obtained were analyzed by calculating the percentage of each item and the average to draw conclusions descriptively. The findings of this study revealed a positive response from teachers and students regarding the use of ICT media in English classes, students felt that learning English using ICT media was more fun and not boring in class, they were also more enthusiastic in participating in English learning in class. class, students also feel more understanding of English material when the teacher uses the TIK or ICT to teach in the classroom. The teacher also responded very well where the teacher agreed with the use of ICT media in the classroom and the teacher felt the benefits of using the media but there were several obstacles faced by the teacher when using ICT, such as operating constraints. This study provides insight into how students and teachers view ICT as a teaching and learning tool that can help provide a better English learning experience, as well as identify the barriers teachers feel when using ICT media.